Impact of removing laver (Porphyra) farming racks on the distribution, diversity and foraging behavior of waterbirds in coastal wetlands in eastern China - Chen, Taiyu; Hu, Wei; Wu, Dawei; Lu, Changhu (Frontiers in Ecology and Evolution, 2025)
IntroductionThe coastal wetlands in eastern China are important feeding and resting sites for migratory waterbirds. Intertidal aquaculture in this region has various effects on waterbird communities, yet research on the impact of coastal restoration on waterbird communities remains limited.MethodsTo explore the impacts of coastal restoration in the Lianyungang coastal wetland, an important staging area for migratory birds along the East Asian-Australasian Flyway (EAAF), we conducted comparative studies on changes in waterbird community structure, behavior composition, and intertidal food resources before and after the removal of laver racks during autumn months from 2020 to 2023.ResultsThe results were as follows: (1) A total of 11544 birds belonging to 37 species were recorded in the study area, including 8 globally threatened or near-threatened species. (2) Following restoration, species richness, abundance, Shannon-Wiener diversity index, and Margalef richness index of waterbirds were significantly higher compared to pre-restoration levels. Notably, the numbers of ducks, plovers, and sandpipers increased significantly, while gull numbers decreased significantly, likely due to habitat structure loss. (3) The proportion of foraging behaviors of 4 common waterbird species increased significantly after restoration, while the percentage of resting behavior significantly decreased. (4) No significant differences in macrobenthos species richness, abundance, biomass or α-diversity indices were detected post-restoration, but the macrobenthos in laver racks area (lower tidal zone) were significantly more abundant than those in the non-racks area (middle tidal zone).DiscussionThe laver farming racks not only occupied intertidal zones with abundant food resources but also limited the ability of some waterbird species to fly and evade predators, while the removal of these racks could restore foraging habitat accessibility by removing physical barriers. Our study revealed the trends in changes in waterbird communities before and after the removal of laver racks, providing practical insight and references for coastal restoration.